Shock Transmission through International Banks: Austria - Esther Segalla (Oesterreichische Nationalbank (OeNB), 2015)
This study provides findings on the transmission of liquidity shocks by Austrian parent banks through the lending channel. I investigate how different types of parent banks adjust their balance sheet positions in response to a liquidity shock and how such an adjustment is transmitted into destination countries. I distinguish between three definitions of crossborder lending activities. In the most general definition I analyze changes in total lending, which consists of the two components - lending to banks and lending to non-banks. In a second step I concentrate on a narrower definition of lending, that is lending to nonaffiliated banks. Finally I focus on an even more targeted definition, such as lending to affiliated banks (lending to branches and subsidiaries). I find that (1) smaller banks (parent banks without affiliates) did not adjust their balance sheet composition in a very pronounced manner in response to a liquidity shock. (2) Large banks (parent banks with affiliates) did decrease moderately their cross-border loan share to other, non-affiliated banks. (3) Internal capital markets are important for the funding structure of Austrian parent banks and their foreign affiliates. (4) Destination countries matter. Countries signing the Vienna Initiative do receive strong support through the internal capital market.
Keywords: E44; F30; G18; G21; G32; 330; cross-border lending; liquidity risk; shock transmission; internal capital markets; Vienna Initiative